Evaluasi Layanan Digital BPJS Kesehatan Di Kantor BPJS Aceh Singkil - Raida; Vellayati Hajad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2023)
This study discusses the evaluation of services in digital form to be able to improve the quality of services at the Aceh Singkil Health BPJS Office. The purpose of this study is to see the development of services provided by the BPJS Health Office to participants through Pandawa services, mobile JKN, Chika (JKN Chat Assistant), and the BPJS Kesehatan Care Center 165. This research method is a qualitative one with a case study approach. The resource persons are: (1) membership staff; (2) benefits guarantee staff; (3) security unit/security guard at the Aceh Singkil Health BPJS Office; and (3) JKN participants. The results of the study show that Pandawa services, mobile JKN, Chika (JKN Chat Assistant), and BPJS Kesehatan Care Center165, where these services can be used by JKN participants without a time limit, can be used anytime and anywhere. These services can be more effective and efficient. The conclusion from this study is that there has been an increase in the quality of services implemented by the BPJS Health Office, and there are many benefits felt by JKN participants or benefits from the BPJS Office.